Flagellate dermatitis following consumption of shiitake mushroom - Hui Voon Loo; Hazel H. Oon (PAGEPress Publications, 2011)
Japanese dermatologists were the first to describe the very characteristic flagellate dermatitis following consumption of under-cooked or raw shiitake mushroom (Lentinus edodes). These similar eruptions were also reported in patients treated with bleomycin, in dermatomyositis and adult onset Still's disease. We report a case where a 40 year old chinese female developed flagellate dermatitis following ingestion of a bun containing shiitake mushroom.